2022
DOI: 10.2196/29196
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to HIV Testing Among Adolescents and Young Adults in Washington, District of Columbia: Formative Research to Inform the Development of an mHealth Intervention

Abstract: Background Adolescents and young adults (AYA) in the United States, and in Washington, District of Columbia (DC), specifically, are disproportionately affected by HIV. Both the national Ending the HIV Epidemic initiative and DC-specific plans emphasize HIV testing, and innovative strategies to encourage testing among AYA are needed. Objective The purpose of this study is to identify sexual behaviors, HIV knowledge, HIV perceptions (eg, susceptibility an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…Wilbourn et al demonstrated that adolescents and young adults with a perceived risk of HIV infection were more likely to undergo testing for HIV infection [31]. Our results also revealed that the number of participants who had ever undergone a self-risk assessment for HIV infection was 166% higher among those who underwent testing for HIV infection than among those who did not.…”
Section: Discussionsupporting
confidence: 63%
“…Wilbourn et al demonstrated that adolescents and young adults with a perceived risk of HIV infection were more likely to undergo testing for HIV infection [31]. Our results also revealed that the number of participants who had ever undergone a self-risk assessment for HIV infection was 166% higher among those who underwent testing for HIV infection than among those who did not.…”
Section: Discussionsupporting
confidence: 63%